Bryan, Alan Lyle (editor): New evidence for the pleistocene peopling of the Americas. Peopling of the Americas Symposia Series. Center for the Study of Early Man, University of Maine, Orono, Maine, 1986. (368 pp. en dos columnas.) - Schobinger, Juan (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Arqueología y Etnología, 1986)

(untitled)
Fil: Schobinger, Juan. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras